Physiological effects of prolactin on early pregnancy loss (Tikrit Journal of Pharmaceutical Sciences, 2023)
Abortion generally presented as two types; the spontaneous and the induced abortion. Spontaneous one is the termination of pregnancy before fetal viability which occurs spontaneously. About 80% of spontaneous abortion losses occur in the first trimester, the incidence decreases with advance in pregnancy. Prolactin is a polypeptide hormone that is synthesized in and secreted from specialized cells of the anterior pituitary gland, the lactotrophs. The major action of prolactin is lactogenesis (milk production). It is the major hormone stimulating the production of milk. Prolactin seems to play an important role in implantation and subsequent placentation in the human endometrium, and it is recognized as a crucial signal for the initiation and maintenance of decidualization. In addition to that, prolactin inhibits the secretion of gonadotropin releasing hormone by the hypothalamus, and this inhibition lead to decreased secretion of luteinizing hormone (LH), which normally initiates ovulation, therefore with hyperprolactinemic state ovulation, does not occur (anovulation). The aim of this study is to study the effects of prolactin hormone in the incidence of abortion cases in first trimester pregnancy in women in Tikrit city. Serum Prolactin was measured by using kit made in France. VIDAS Prolactin (Made in Italy), for the enzyme immunoassay determination of human prolactin in human serum or plasma by using the technique of Enzyme Linked Fluorescent Assay (ELFA). One hundred and thirty four pregnant women were participated & finished the whole study; 56 normal pregnant women in first trimester as a control group and 78 women with different types of abortion in first trimester who are diagnosed by clinical examination and/or by ultrasonography as aborted group. Seventy eight aborted women were participating in the present study. Threatened abortion was the highest one among aborted women (44.9%). Followed by missed abortion (19.23%), incomplete abortion (14.1%), complete (9%), inevitable (7.69%) & the last is recurrent (2.57%). Regarding serum prolactin, there is a significant difference between normal pregnant women (47.1 ± 25.4 ng/ml) as compare with aborted women (69.4 ± 48.8 ng/ml). In another word, aborted women have a serum prolactin concentration than that of normal pregnant women (p≤0.01).